The effectiveness of flipped classroom on scientific literacy and critical thinking improvement - Nur Wijayanto; Abdul Gani; M. Hasan; Asri Widowati (Jurnal Pendidikan Kimia (JPKIM), 2023)
Scientific literacy has a vital role in supporting 21st-century skills. Good literacy skills can directly affect students' thinking abilities, which makes them more creative in solving problems. The low ability of students' scientific literacy and critical thinking is still a problem in the world of education. The application of appropriate learning models and methods can improve student learning outcomes. The goal of this study was to see how the flipped classroom learning model affected the literacy and critical thinking skills of SMAN 3 Yogyakarta grade XI students. The pretest-posttest control design experimental method was carried out on a total of 35 samples from a population of 213 students. The results of the Mann Whitney and Wilcoxon tests obtained a significance of less than 0.05 in both the control and experimental groups for pretest and posttest values. The use of the flipped classroom method effectively improved scientific literacy and critical thinking skill. There is a strong relationship between critical thinking skills and scientific literacy.Keywords: Critical thinking; Flipped classroom model; Literacy science; 21st century skill